Association between IGF-1 levels and MDD: a case-control and meta-analysis - Qiao, Xin; Yan, Jiaxin; Zang, Zongjun; Xi, Lei; Zhu, Wenli; Zhang, En; Wu, Lijuan (Frontiers in Psychiatry, 2024)
Purpose: Insulin-like growth factor-1 (IGF-1) has a variety of neurotrophic effects, including neurogenesis, remyelination and synaptogenesis, and is an effective regulator of neuronal plasticity.Although multiple studies have investigated IGF-1 in depression-related disorders, few studies have focused on patients with a first episode of clearly diagnosed depression who had never used antidepressants before.. Therefore, this study investigated first-episode and drug-naïve patients with depression to supplement the current evidence around IGF-1 levels in depressive disorders.This study consisted of two parts. In the first part, 60 patients with firstepisode and drug-naïve depression and 60 controls matched for age, sex, and BMI were recruited from the outpatient department of the Fourth Hospital of Wuhu City, and the community. The casecontrol method was used to compare differences in serum IGF-1 levels between the two groups. In the second part, 13 case-control studies were screened through the database for meta-analysis to verify the reliability of the results.Results: Results of the case-control study demonstrated that serum IGF-1 levels are significantly higher in patients with first-episode and drug-naïve depression compared to healthy controls (p<0.05), although there was no significant difference between men and women with diagnosed MDD, there was no significant correlation between serum IGF-1 level and age in patients with depression and no significant correlation between IGF-1 level and the severity of depression. The meta-analysis corroborates these findings and demonstrated that IGF-1 levels are significantly higher in MDD patients than in healthy controls.Patients with first-episode and drug-naïve depression have higher IGF-1 levels, but the exclusion of confounding factors in studies of IGF-1 as it relates to depressive disorders must be taken into consideration strictly, and additional research is needed to fully understand the critical role of IGF-1 in depression